Explaining Irrational Actions (2017)
We sometimes want to understand irrational action, or actions a person undertakes given that their acting that way conflicts with their beliefs, their (other) desires, or their (other) goals. What is puzzling about all explanations of such irrational actions is this: if we explain the action by offering the agent’s reasons for the action, the action no longer seems irrational, but only (at most) a bad decision. If we explain the action mechanistically, without offering the agent’s reasons for it, then the explanation fails to explain the behavior as an action at all. I focus on cases that result from compulsion or irresistible desire, especially addiction, and show that this problem of explaining irrational actions may be insurmountable because, given the constraints on action explanations, we cannot explain irrational actions both as irrational and as actions.